Clinical, biochemical, and genetic features associated with VARS2‐related mitochondrial disease. Issue 4 (7th February 2018) - Bruni, Francesco; Di Meo, Ivano; Bellacchio, Emanuele; Webb, Bryn D.; McFarland, Robert; Chrzanowska‐Lightowlers, Zofia M.A.; He, Langping; Skorupa, Ewa; Moroni, Isabella; Ardissone, Anna; Walczak, Anna; Tyynismaa, Henna; et al.
Abstract: In recent years, an increasing number of mitochondrial disorders have been associated with mutations in mitochondrial aminoacyl‐tRNA synthetases (mt‐aaRSs), which are key enzymes of mitochondrial protein synthesis. Bi‐allelic functional variants in VARS2, encoding the mitochondrial valyl tRNA‐synthetase, were first reported in a patient with psychomotor delay and epilepsia partialis continua associated with an oxidative phosphorylation (OXPHOS) Complex I defect, before being described in a patient with a neonatal form of encephalocardiomyopathy. Here we provide a detailed genetic, clinical, and biochemical description of 13 patients, from nine unrelated families, harboring VARS2 mutations. All patients except one, who manifested with a less severe disease course, presented at birth exhibiting severe encephalomyopathy and cardiomyopathy. Features included hypotonia, psychomotor delay, seizures, feeding difficulty, abnormal cranial MRI, and elevated lactate. The biochemical phenotype comprised a combined Complex I and Complex IV OXPHOS defect in muscle, with patient fibroblasts displaying normal OXPHOS activity. Homology modeling supported the pathogenicity of VARS2 missense variants. The detailed description of this cohort further delineates our understanding of the clinical presentation associated with pathogenic VARS2 variants and we recommend that this gene should be considered in early‐onset mitochondrial encephalomyopathies or encephalocardiomyopathies. Abstract : Here we describe in detail the clinical, biochemical and genetic features of 13 patients, from 9 unrelated families, harboring mutations in VARS2, the gene encoding for the mitochondrial valyl tRNA‐synthetase. All patients except one, who manifested with a less severe disease course, presented at birth exhibiting severe encephalomyopathy and cardiomyopathy. We recommend that VARS2 should be considered in early‐onset mitochondrial encephalomyopathies or, encephalocardiomyopathies. (VARS2).